1996
DOI: 10.1097/00006534-199609001-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Analysis of Changes in the Nasolabial Fold Using Magnetic Resonance Imaging: Implications for Facial Rejuvenation and Facial Animation Surgery

Abstract: An anatomic study was performed on living subjects using magnetic resonance imaging (MRI) to distinguish the relative contribution of skin, subcutaneous tissue, and muscle to dynamic changes in the nasolabial fold during facial animation and aging. MRI scans with the face in repose and then holding a full smile were performed in both young and old adult subjects. Anatomic landmarks were identified, and measurements characterizing their position were made on the MRI console. MRI resulted in excellent image reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…115: , 2005 Numerous authors have investigated changes in the aging midface. [1][2][3][4][5] On the basis of objective studies, surgeons have modified their techniques for facial rejuvenation commensurate with their ongoing analysis of changes that accompany the aging process. 6 -8 Therefore, it remains essential to continue to provide quantitative analysis of soft-tissue changes in the midface that occur as we age.…”
mentioning
confidence: 99%
“…115: , 2005 Numerous authors have investigated changes in the aging midface. [1][2][3][4][5] On the basis of objective studies, surgeons have modified their techniques for facial rejuvenation commensurate with their ongoing analysis of changes that accompany the aging process. 6 -8 Therefore, it remains essential to continue to provide quantitative analysis of soft-tissue changes in the midface that occur as we age.…”
mentioning
confidence: 99%
“…33,34 This chronic passive pulling of the attachments may explain the thickening of the fat and skin over the nasolabial area on magnetic resonance studies. 35 From the physiologic point of view, the development of the nasolabial fold involves the smiling mechanism, the interaction of dynamic and static soft tissues of the cheek, and variations in facial architecture, all of which combine to form different configurations in distinct individuals. 32 The complexity of the associated anatomy and physiology makes it very difficult to postulate a unique treatment and explains why this region is resistant to rejuvenation.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent research, MRI was used to evaluate the relative contribution of the skin, subcutaneous tissue and muscles in the formation of the nasolabial fold while smiling and at rest. It was found that there is a thickening of the inferior region of the malar fat and an expansion of the skin around the same area without changes in the levator muscles of the lip (24). These findings would be related to the fact that during smiling, there is a shortening of the levator labial commisure that produces pressure over the malar fat and the skin inferior to the cheek.…”
Section: Discussionmentioning
confidence: 99%